Pseudomonas aeruginosa Exhibits Directed Twitching Motility Up Phosphatidylethanolamine Gradients - Kearns, Daniel B. (American Society for Microbiology, 2001)
Pseudomonas aeruginosa translocates over solid surfaces by a type IV pilus-dependent form of multicellular motility known as twitching. We wondered whether cells utilize endogenous factors to organize twitching, and we purified from wild-type cells a lipid that caused directed movement. Wild-type P. aeruginosa, but not a pilJ pilus-deficient mutant, showed biased movement up gradients of phosphatidylethanolamine (PE) established in agar. Activity was related to the fatty acid composition of the lipid, as two synthetic PE species, dilauroyl and dioleoyl PE, were capable of directing P. aeruginosa motility while many other species were inactive. P. aeruginosa PE did not contain either laurate or oleate, implying that the native attractant species contains different fatty acids. Uniform concentrations of PE increased cell velocity, suggesting that chemokinesis may be at least partly responsible for directed movement. We speculate that PE-directed twitching motility may be involved in biofilm formation and pathogenesis.